Minimizing the Cost of Overstocking: Towards a Thinning Regime for Community - Managed Pine Plantations in the Central Hills of Nepal (Journal of Forest and Livelihood, 2024)
The authors assess the impact of stocking levels on the growth of Pinus Roxburghii and Pinus Patula which were planted in the two central hill districts of Nepal over the past two decades, and are generally overstocked due to conservative thinning practices. An analysis of more than 150 tress at different stocking levels showed that overstocking has reduced volume growth, and if thinning is delayed, this will be equivalent to a loss of over USD 200 per hectare per anum. To maximize income from such plantations, thinning regimes for the two species are also suggested.